Bicycle tyres – Development of a new test-rig to measure mechanical characteristics. (October 2022) - Dell'Orto, G.; Ballo, F.M.; Mastinu, G.; Gobbi, M.
Highlights: Tyre characteristics are crucial for bicycle dynamics. Test-rigs for bicycle tyres ensure repeatability of measurements. Uncertainty model has been developed and the results validated. Lateral force and self-aligning moment were measured through the new test-rig. Abstract: Bicycles will be largely exploited in city mobility, as a smart and cheap tool to achieve the goals of reducing air pollution levels and increasing the liveability of cities. Their growing popularity requires more knowledge on bicycle dynamics to prevent instability. In this context, tyres may play a crucial role, as already stated in literature (European Environment Agency, 2019, 1). This is why proper test-rigs are needed to obtain reliable tyre parameters. The paper presents Vetyt, acronym of "Velo Tyre Testing", a new test-rig specifically developed for bicycle tyres at the Department of Mechanical Engineering of Politecnico di Milano. The development procedure is described step by step, enlightening the main goals achieved. Vetyt frame was reinforced to test tyres on flat track, with vertical loads up to 550 N. After that, a new air-cooling system to keep constant the temperature of the rolling surface was added. An uncertainty model was developed on theoretical basis, and a static verification of forces recorded by Vetyt was performed. At the end, the results coming from a very first experimental campaign are presented. Lateral forces and self-aligning moments are depicted for racing road bicycle tyre, for vertical loads of 400 N and 490 N. The variation of camber angle (tested up to ±10°) contributes to the increase in magnitude of the values of lateral force and self-aligning moment.